2018
DOI: 10.1007/s11064-018-2578-8
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligase c-cbl Inhibits Microglia Activation After Chronic Constriction Injury

Abstract: E3 ubiquitin ligase c-Caritas B cell lymphoma (c-cbl) is associated with negative regulation of receptor tyrosine kinases, signal transduction of antigens and cytokine receptors, and immune response. However, the expression and function of c-cbl in the regulation of neuropathic pain after chronic constriction injury (CCI) are unknown. In rat CCI model, c-cbl inhibited the activation of spinal cord microglia and the release of pro-inflammatory factors including tumor necrosis factor alpha (TNF-α), interleukin 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…C-Cbl and Cbl-b are two members of Cblfamily E3 ligases that display a high degree of sequence similarity (7). Peripheral nerve injury has been shown to reduce the protein level of C-Cbl in spinal cord microglia, which allows for the microglia activation and subsequent release of proinflammatory factors (15). Our data demonstrated that CFA injection did not influence the total Cbl-b expression in spinal dorsal horn of adult mice.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…C-Cbl and Cbl-b are two members of Cblfamily E3 ligases that display a high degree of sequence similarity (7). Peripheral nerve injury has been shown to reduce the protein level of C-Cbl in spinal cord microglia, which allows for the microglia activation and subsequent release of proinflammatory factors (15). Our data demonstrated that CFA injection did not influence the total Cbl-b expression in spinal dorsal horn of adult mice.…”
Section: Discussionmentioning
confidence: 57%
“…2B). As well, C-Cbl, the Cbl-b homology protein that is also present in the spinal cord and is involved in pain processing (15), did not interact with GluN2B (Fig. 2B).…”
Section: Cbl-b Specifically Interacts With Nmdar Subunit Glun2bmentioning
confidence: 92%